a) n+3 chia hết cho n-2
=>n-2+5 chia hết cho n-2
=> 5 chia hết cho n-2
U(5)=1;5
=>n=3;7
Ta có: n + 3 chia hết cho n - 2
<=> n - 2 + 5 chia hết n - 2
=> 5 chia hết n - 2
=> n - 2 thuộc Ư(5) = {-1;1;-5;5}
=> n = {1;3;-3;7}
b)\(\frac{2n+5}{n+1}=\frac{2\left(n+1\right)+3}{n+1}=\frac{2\left(n+1\right)}{n+1}+\frac{3}{n+1}=2+\frac{3}{n+1}\in Z\)
=>3 chia hết n+1
=>n+1 thuộc Ư(3)={1;3} (vì n thuộc N)
=>n thuộc {0;2}
c)\(\frac{4n+3}{2n+6}=\frac{2\left(2n+6\right)-9}{2n+6}=\frac{2\left(2n+6\right)}{2n+6}-\frac{9}{2n+6}=2-\frac{9}{2n+6}\in Z\)
=>9 chia hết 2n+6
=>2n+6 thuộc Ư(9)={1;3;9} (vì n thuộc N)
=>n thuộc rỗng